1999
DOI: 10.1046/j.1525-1497.1999.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Rewarding teaching faculty with a reimbursement plan

Abstract: OBJECTIVE:To develop a system for measuring the teaching effort of medical school faculty and to implement a payment system that is based on it.DESIGN: An interventional study with outcomes measured before and after the intervention. SETTING:A department of internal medicine with a university hospital and an affiliated Veterans Administration hospital. INTERVENTION:We assigned a value in teaching units to each teaching activity in proportion to the time expended by the faculty and the intensity of their effort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] A 2006 systematic review of implemented incentive compensation system (ICS) programs in academic units concluded that incentive compensation was associated with positive financial impact and increased professional productivity in clinical and scholarly activity. 9 Despite the intuitive benefit of rewarding performance with incentive pay, the application of self-determination theory to compensation systems suggests that the autonomous motivation of an individual can be harmed by an ICS.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] A 2006 systematic review of implemented incentive compensation system (ICS) programs in academic units concluded that incentive compensation was associated with positive financial impact and increased professional productivity in clinical and scholarly activity. 9 Despite the intuitive benefit of rewarding performance with incentive pay, the application of self-determination theory to compensation systems suggests that the autonomous motivation of an individual can be harmed by an ICS.…”
mentioning
confidence: 99%
“…3,4 Similarly, approaches exist to calculate and compensate teaching productivity for clinician-educators via a relative teaching unit or RTU model. 5 To our knowledge, however, a model to compensate non-researcher-clinicians for participating in clinical and translational research initiatives does not exist, yet is sorely needed. Indeed, without providing incentives for clinicians to participate in research activities, it is unlikely that they will do so in the numbers needed to fully realize the investments being made to advance medical science and health care delivery.…”
Section: Existing Compensation Modelsmentioning
confidence: 99%
“…United States medical schools have adopted different approaches to assessing the amount of work performed in medical student education, ranging from a simple count of contact hours to complicated models involving relative value units (RVUs) similar to that used to quantify clinical workload. [1][2][3][4][5][6][7][8][9][10][11][12][13] As opposed to instruction on rounds or in clinic, more preparation is often required for teaching preclinical medical students. Some institutions that measure academic workload incorporate preparation time in their estimates, although the practice is not universal.…”
Section: Introductionmentioning
confidence: 99%
“…Some institutions that measure academic workload incorporate preparation time in their estimates, although the practice is not universal. 1,2,5,6,7,9,10,11,13 and the amount recognized varies markedly (ranging from one to 15 hours per student contact hour). 1,2,5,6,11 In the literature, attention has focused on time accounting for clinical education, with few studies concentrating on preclinical (specifically didactic and pathology) medical teaching.…”
Section: Introductionmentioning
confidence: 99%